PENGARUH PENDEKATAN SAINTIFIK BERBANTUAN MEDIA FLIPBOOK TERHADAP PENINGKATAN KEMAMPUAN LITERASI SAINSSISWA SEKOLAH DASAR - Ayu Utami, Neng Riski; Sofyan Iskandar; Fitri Nuraeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Scientific literacy skills are very important for improving the learning process, especially in science lessons. The low scientific literacy abilities of elementary school students are the background for this research. This research aims to determine the effect of the scientific approach assisted by flipbook media on increasing students' scientific literacy skills and to determine the increase in scientific literacy of students who receive learning using the scientific approach assisted by flipbook media better than students who receive conventional learning. The research method used was quasi-experimental with a non-equivalent pretest-posttest control group design on the subject of energy changes. The research sample was class III elementary school, consisting of class III A as the experimental class and III B as the control class. The results of data analysis show that there is an influence of the scientific approach model assisted by flipbook media on students' scientific literacy skills of 56.1%. The results of the n-gain test show that the experimental class with the scientific approach assisted by digital flipbooks is at a medium interpretation of 0.4868. In contrast, the control class uses the model. Conventional learning is at a moderate interpretation of 0.3339, which means that students who receive science learning using a scientific approach model assisted by flipbook media are better than students who receive conventional learning.   Keywords: scientific literacy ability, flipbook media, scientific approach